OUR EXPERIENCE OF RADIOLOGIC DIAGNOSIS OF POST COVID-19 MANIFESTATIONS OF THE FACIAL AND JAW OSTEOMYELITIS - O.R. Teshaev,; G.E. Rakhmonova,; D.Z. O‘ktamova,; D.Z. O‘ktamov, (Central Asian Journal of Medicine, 2025)
The inflammatory process after COVID-19 can affect not only the lungs, but also other organs and tissues, including facial bones. This activation of the immune system contributes to osteolysis and infection of bone tissues, resulting in the development of osteomyelitis. Osteomyelitis of the maxillofacial bones after Covid-19 was manifested in 76 patients with various signs and symptoms. Patients may also have symptoms of an infectious process such as pain and swelling in the facial area, redness of the skin, increased sensitivity of the bones and soft tissues, fever and purulent discharge. It is important to note that the clinical presentation of post-Covid osteomyelitis may differ in patients depending on various factors, including the level of bone and tissue involvement and the general condition of the patient [1,2]. In postcomitant osteomyelitis of the facial bones, there are peculiarities of surgical tactics. Face-jaw osteomyelitis was more common in patients over 40 years of age (47%) and clinical signs of the disease were: pain in the face-jaw area was 83.3%, bad breath from the mouth was 33.3%, and istination was 30%. Of the destructive changes, the destruction of the lower jaw alveolar part was observed in 90%, the destruction of the upper jaw alveolar part was observed in 88.3%, the destruction of the palate and oblique bone was observed in 76.7%, and the destruction of the lower part of the forehead bone was observed in 73.3%. Surgical treatment may be required in cases where conservative treatment is ineffective or there are complications that require surgical intervention. The primary goal of surgical tactics includes the removal of infected and necrotic tissue, restoration of normal anatomy, and functional rehabilitation of the patient. Drainage and curettage are the primary stage of surgery for postcoatoid osteomyelitis.